THU0470 Work and professional recognition in fibromyalgia patients – a national french web based survey on sick leave in 1870 fibromyalgia female patients. (15th June 2017) - Laroche, F; Azoulay, D; Guérin, J; Coste, J; Perrot, S
Abstract : Background: Fibromyalgia (FM) induces work limitations with an increase of number of days of sick leave 3 to 4 fold higher (1, 2). Objectives: Our objectives were to analyze work status, to determine risk factors for sick leave and to compare women working to women in sick leave during the past 12 months in a female population with FM. Methods: 1870 female workers suffering from FM were selected from a large internet-based national survey of 4516 responders (Fibromyalgie-SOS Association website in France in 2014). Women having a FIRST score ≥5/6 were included. Results: 1870 patients participated to the survey: 955 with full time job, 149 with part time job (related to FM status) and 766 on sick leave (7% 1–3 months, 27.3% 3–12 months and 62% >12 months). Fibromyalgia Impact questionnaire (FIQ) score was slightly lower in the 1104 patients currently working compared to the 766 on sick leave (56 versus 58.7), but not clinically different. 64, 5% of the population have been on sick leave during the last 12 months (average duration: 37 mean days for full time job and 122 among those with part time job). Women being in sick leave were older (p<0, 0001), single (p=0, 0321), had less financial income (p<0, 0001), used more antidepressants (p=0, 0085) and more anti epileptics (p=0, 0102). Recognition of FM by occupational physicians or social security doctors were lower among the workers (p<0.0001). In the 1104 currently working, more than 33% have never been visiting their occupational physician and 44, 2% rarely. They reported no support from these doctors (p=0, 0011) particularly those having not being on sick leave. Independent criteria of sick leave were transportation time (p=0.0131), work difficulties (p=0.0031), hinders career progress (p=0.0196), sedentary occupation and repetitive work (p=0.0195). Conclusions: These data on a large fibromyalgia population shows that clinical status and also professional factors may influence work ability and sick leave. The work factors include work difficulties, transportation time, sedentary and repetitive occupation. These results should be taken into account by the work professionals in order to facilitate work capacity in FM patients. References: Sicras-Mainar A, Rejas J, Navarro R, Blanca M, Morcillo A, Larios R, Velasco S VillarroyaC. Treating patients with fibromyalgia in primary care settings under routine medical practice: a claim database cost and burden of illness study. Arthritis Research & Therapy 2009, 11:R54. White K. Comparing self-reported function and work disability in 100 community cases of fibromyalgia syndrome versus controls in London, Ontario: the London Fibromyalgia Epidemiology Study. Arthritis Rheum. 1999;42:76–83. Acknowledgements: Fibromyalgia SOS french Association. Disclosure of Interest: None declared